Residual stress and deformation analysis in machining split straight bevel gears - Wang, Bin (Strojniški vestnik, 2021)
In the machining of split straight bevel gears, the stiffness changes and internal stress are redistributed, which leads to serious deformation of the gear blank after machining. To rectify this problem, q finite element model is established by transforming the processing information of the gear blank into the finite element simulation calculation information, and the gear machining simulation of split straight bevel gear is carried out. Considering the material, design, and machining process of the gear blank, the characteristics and laws of internal stress variation during the gear machining are studied, and the internal mechanism and deformation law of split straight bevel gear are explored. Finally, the gear machining experiment, and the gear blank measurement are carried out. The results show that the deformation law of simulation is consistent with that of the experiment and the deformation characteristics of the split straight bevel gear are consistent with the change law of initial residual stress.
Keywords: deformacija po obdelavi; deformation measurement; finite element model; machining deformation; meritev deformacije; model s končnimi elementi; preostale napetosti; residual stress; segment stožčastega zobnika; simulacija obdelave; split straight bevel gear; zobnik z ravnimi zobmi